#FeesMustFall and decolonising the curriculum: Stellenbosch University students’ and lecturers’ reactions - Costandius, E.; Blackie, M.; Nell, I.; Malgas, R.; Alexander, N.; Setati, E.; Mckay, M. (South African Journal of Higher Education, 2018)
In South African higher education institutions, the student protests of 2015–2016 called for the decolonisation of higher education spaces and equal access to these spaces. We collected data from students and lecturers over the period of one year in order to better understand the reactions of students and lecturers and the effects the protests had on their experiences. Perspectives of affective theory, decolonisation and social justice theories were used. It was discovered that the protests had a great affective impact on participants. Strong emotions and beliefs affected the relationships between students and lecturers and African centrality was suggested as a framework for curriculum change. Some settler perspectives emerged and polarisation was evident. It is our hope that lecturers could use this research to assist them in decolonising their spaces of teaching and learning.